ANALISA PERBANDINGAN BIAYA PEMBANGKIT LISTRIK TENAGA SURYA OFF-GRID, DENGAN GENERATOR SET DAN PERUSAHAAN LISTRIK NEGARA DI PT. KIPRA SARANA DUTA AGUNG - Putranto, Ferry; Nempung, Judo Ignatius; Widodo, Bambang (Prodi Teknik Elektro FT UKI, 2024)
Electricity is a vital necessity in modern life, but the increasing demand for energy presents significant challenges, especially due to the depletion of natural resources like petroleum in Indonesia. Renewable Energy (RE), particularly solar energy, offers a sustainable solution. Solar Power Plants (PLTS) harness solar energy, an unlimited resource, which has great potential in Indonesia. However, the adoption of PLTS is still hindered by high initial investment costs. This study compares the cost-effectiveness and operational efficiency between Off-grid PLTS, Generators, and PLN electricity at PT. Kipra Sarana Duta Agung. The results show that while the initial investment for PLTS is higher, its operational costs are very low because it requires no fuel or routine maintenance, making it the most economical and environmentally friendly option in the long term. Off-grid PLTS also offers energy independence by storing backup energy in batteries. In contrast, Generators require diesel fuel costs and regular maintenance, while PLN electricity requires ongoing monthly payments. The study concludes that Off-grid PLTS is a more efficient and sustainable energy solution with a payback period of six years. Additionally, Off-grid PLTS aligns with government policies promoting RE as a long-term solution to the depletion of fossil fuels and rising energy costs. Keywords : Cost Comparison Off-Grid PLTS, Generators, and PLN